PENGARUH KEBIJAKAN DIVIDEN, NILAI TUKAR, LEVERAGE, DAN FIRM SIZE TERHADAP VOLATILITAS HARGA SAHAM - Selpiana, Komang Ria; Badjra, Ida Bagus (E-Jurnal Manajemen; Vol 7 No 3 (2018), 2018)
Stock price volatility is movement decrease or increase of the stock price. The purpose of this research is to determine impact of dividend policy, exchange rate, leverage, and firm size to stock price volatility. This research was conducted on the stock of LQ45 Index companies in the period of 2012 - 2016. Sample in this research amount 24 company by the sensus method. The analysis technique used is multiple linear regression analysis. Based on the results of the analysis found that the policy of dividend, exchange rate, leverage, and firm size simultaneously have a significant effect on stock price volatility. Partially dividend policy has a significant positive effect on stock price volatility, exchange rate has positive significant effect to stock price volatility, leverage has positive effect not significant to stock price volatility, firm size has significant negative effect to stock price volatility. Keywords: Volatility, Dividend, Exchange Rate, Leverage, Size